A POTRET PERKEMBANGAN IMPLEMENTASI KEBIJAKAN PROGRAM BUMDES DI INDONESIA; ANALISIS BIBLIOMETRIK - Ihin Solihin; Jumanah Jumanah; Julizar Idris; Elyana Thusyadiah; Nofa Rahmadini; Masayu Indah Meiliana (Asia-Pacific Journal of Public Policy, 2023)
The existence of BUMDes (a village-owned enterprise) as one of the strategies to support the achievement of village goals for development, particularly in enhancing the village economy and welfare for village communities, necessitates the implementation of BUMDes policies in the form of programmes or policy derivatives. The village is responsible for managing and regulating the community's interests in accordance with local conditions and sociocultural norms. This study utilises secondary data methods and literature reviews to collect and process data from Google Scholar library data sources. According to the findings of this study, the BUMDES is one of the village's programmes to improve economic facilities and village welfare. Therefore, cooperation between the village government and the community is required to promote village development, as development in this village directly benefits the surrounding community